Number of chronic diseases and cognitive function among the elderly in China: a moderated mediation model - Feng, Xiaoling; Peng, Jie; Cao, Xiaoying; Lai, Lichong; Huang, Dongmei; Tao, Pinyue; Pan, Xiao; Pan, Qini; Fan, Dejing; Lu, Shuyu; Li, Caili; Pan, Yanfei; et al. (Frontiers in Psychology, 2025)
PurposeDespite the wealth of data on the role of chronic disease comorbidity in shaping cognitive dysfunction in older adults, a comprehensive view of this dynamic interplay remains a frontier. This study will reveal the intricate interactions between the number of chronic diseases and cognitive function in the elderly, based on the perspective of cognitive function in patients with multiple chronic diseases.MethodsOur study was based on the data from the 2023 China Psychological Care for the Elderly Action Survey, and the SPSS 26.0 (IBM Corp., Armonk, NY, United States) software package was used for mediation model analysis. The approach encompassed descriptive analysis of variables, Spearman’s correlation analyses to explore associations between variables, and a moderated mediation analysis.ResultsThe study found that the number of chronic diseases (r = 0.183, p < 0.001) was positively correlated with cognitive function. Anxiety and depression partially mediated the relationship between the number of chronic diseases and cognitive function (β = 0.227, 0.235, both p < 0.001). Age moderated the association between the number of chronic diseases and depression (β = 0.010, p < 0.001).ConclusionThis study provides a comprehensive mediation model that establishes a new association between the number of chronic diseases and cognitive function in older adults. It suggests that we should pay attention to the negative impact of multiple chronic diseases on cognitive function of the elderly and improve their psychological coping ability, so as to ensure the stable development of healthy aging.